Evaluation of the health pathway through the patient-experience in the French program PAERPA. (13th November 2019) - Donio, V; Defebvre, M M; Pamart, R; Caron, B; Delval-Bugny, C; Dambre, D; Di Martino, C; Beuscart, J B
Abstract: : The patient-experience is an emerging concept in research and medico-social action, and its consideration in the development of care pathways is encouraged (e.g. 'Ma Santé 2020' national plan in France). In addition, the patient-experience of the elderly subject has specific dimensions and his collection presents difficulties insufficiently explored. PAERPA (elderly people at risk of loss of autonomy), French national experiment for the care of frail elderly patients, offers an opportunity to return to these issues. The objective of this study, mandated by the ARS of Hauts-de-France, was to collect the experience of the elderly PAERPA. Faced with the difficulties of current methodologies, several methodological approaches have been combined: semi-structured individual interviews face-to-face or by telephone, dedicated questionnaire. In addition, a specific grid was developed to explore the home-based patient experience, including seven dimensions of the patient-experience identified in the literature. This study was conducted in the second half of 2018 (3 years and a half of the start of the project). The experience of 43 seniors and / or caregivers was collected. Patients PAERPA are generally satisfied with their care but they have difficulties in making the link between their care and the actors and devices specific to PAEPRA experimentation. Human connection and listening seem essential for the elderly patients included. Other dimensions, such as stakeholder coordination, remain controversial and more difficult to grasp. Methodologically, the particular situation of seniors, such as sensory or memory disorders, requires a major adaptation of the survey tools. In PAERPA, the patient-experience of the frail elderly subject passes mainly through the feeling of a human connection. Current methodologies do not seem fully adapted to collectively capture the experience of frail elderly patients. Key messages: Evaluating the patient-experience to improve the health pathway is possible and necessary through a qualitative collection, regularly, in itinere. The peculiarities of older people often require the participation of carers, who need to be involved in the assessment of the patient-experience and raised awareness.